2019
DOI: 10.1111/ene.14026
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate and risk of poor outcomes after stroke

Abstract: Background and purpose The relationship of the estimated glomerular filtration rate (eGFR) with complications after stroke has not been fully characterized for the entire clinical spectrum of eGFR and for the fluctuation in eGFR during hospital stay. Methods Data from the Norfolk and Norwich Stroke Registry recorded between January 2003 and April 2015 were analysed. eGFR was categorized into six clinically relevant categories as per the Kidney Disease Improving Global Outcomes guidelines. The change in eGFR du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The results of our study are consistent with previous literature highlighting the association between CKD and adverse AIS in‐hospital outcomes 7 . Furthermore, our results highlight that CKD patients without ESRD exhibited relatively small increases (4–13%) in the odds of adverse outcomes, while ESRD was associated with higher increases (34–106%), consistent with the previously reported dose‐response relationship between decreasing glomerular filtration rate and adverse AIS outcomes 7 . In terms of thrombolysis for AIS, previous investigations found that CKD was associated with adverse outcomes amongst AIS patients receiving thrombolysis, 11,12,13,24,37,38 thus highlighting CKD as a potential contraindication to thrombolysis for stroke.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results of our study are consistent with previous literature highlighting the association between CKD and adverse AIS in‐hospital outcomes 7 . Furthermore, our results highlight that CKD patients without ESRD exhibited relatively small increases (4–13%) in the odds of adverse outcomes, while ESRD was associated with higher increases (34–106%), consistent with the previously reported dose‐response relationship between decreasing glomerular filtration rate and adverse AIS outcomes 7 . In terms of thrombolysis for AIS, previous investigations found that CKD was associated with adverse outcomes amongst AIS patients receiving thrombolysis, 11,12,13,24,37,38 thus highlighting CKD as a potential contraindication to thrombolysis for stroke.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study are consistent with previous literature highlighting the association between CKD and adverse AIS in‐hospital outcomes 7 . Furthermore, our results highlight that CKD patients without ESRD exhibited relatively small increases (4–13%) in the odds of adverse outcomes, while ESRD was associated with higher increases (34–106%), consistent with the previously reported dose‐response relationship between decreasing glomerular filtration rate and adverse AIS outcomes 7 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations